DEVELOPMENT OF ENDURANCE OF TEENAGERS IN SPORTS SCHOOLS IN ATHLETICS (Conferencea, 2023)
The article discusses the development of endurance of adolescents in athletics. Give students' qualities recommendations for the development of physical